O32 The interleukin 22//neutrophil axis is associated with treatment resistance in ulcerative colitis. (19th June 2022) - Pavlidis, Polychronis; Tsakmaki, Anastasia; Pantazi, Eirini; Li, Katherine; Cozzetto, Domenico; Yang, Feifei; Lo, Jonathan; Alberts, Ms Elena; Costa Sa, Ana Caroline; Niazi, Umar; Friedman, Joshua; Long, Anna; et al.
Abstract : Introduction: Interleukin (IL) 22 is a key cytokine involved in regulation of epithelial function and its role in IBD remains highly controversial. Some studies indicate a protective role in epithelial regeneration, whereas other studies imply a pro-inflammatory role. Insights are now needed to improve of understanding of the functional role of this important cytokine and how its expression might impact patients with ulcerative colitis (UC). In this study, we have probed the clinical and functional significance of IL-22 responsive transcriptional modules and causal networks in diseased tissue of over 500 UC patients and in preclinical models of colitis. Methods: We mapped the transcriptional landscape of human colonic epithelial 3D mini-gut organoids in response to treatment with IL22, and other pro-inflammatory cytokines. We tested the clinical significance of the IL22-regulated transcriptome by probing whole colonic biopsies from 550 ulcerative colitis (UC) patients from UNIFI clinical trial programme (patients with UC treated with ustekinumab, an anti-IL12p40 antibody). The functional role of IL22 regulated biological pathways were evaluated in pre-clinical models of UC. Results: IL-22 regulated pro-inflammatory biological pathways involved in microbial recognition, cancer and immune cell chemotaxis. IL-22 was an especially potent regulator of the CXC family chemokines CXCL1, CXCL2, CXCL5, CXCL6 and CXCL8, which are all powerful neutrophil-selective chemokines. There was a positive correlation between the IL-22 transcriptional programme and the histological severity of inflammation (r=0.49, p<0.0001) and, in particular, neutrophil infiltration in lamina propria and the colonic epithelium of patients with UC. Patients with the greatest magnitude of enrichment for IL22-responisve transcripts in whole colonic biopsies sampled immediately prior to ustekinumab initiation was associated with failure to achieve mucosal healing (8%) in comparison with patients with low enrichment scores (25%, P=0.002) at week 8 following induction. IL-22-mediated transcriptional regulation of CXC-family neutrophil-active chemokine expression was highly conserved across species and was dependent on JAK1/STAT3 signalling. In preclinical models of colitis, IL-22 induction of neutrophil-active chemokines was functionally and pathologically important in the recruitment of CXCR2 + neutrophils to the colon. Conclusions: The interleukin 22/neutrophil axis is functionally important in colitis and is associated with treatment resistance in ulcerative colitis